Breaking bad news: A mix methods study reporting the need for improving communication skills among doctors in Pakistan - Muhammad Ahmed Abdullah; Babar Tasneem Shaikh; Kashif Rehman Khan; Muhammad Asif Yasin (BMC, 2024)
Abstract Background Effective skills and training for physicians are essential for communicating difficult or distressing information, also known as breaking bad news (BBN). This study aimed to assess both the capacity and the practices of clinicians in Pakistan regarding BBN. Methods A cross-sectional study was conducted involving 151 clinicians. Quantitative component used a structured questionnaire, while qualitative data were obtained through in-depth interviews with 13 medical educationists. The responses were analyzed using descriptive statistics and thematic analysis. Results While most clinicians acknowledged their responsibility of delivering difficult news, only a small percentage had received formal training in BBN. Areas for improvement include time and interruption management, rapport building, and understanding the patients' point of view. Prognosis and treatment options were not consistently discussed. Limited importance is given to BBN in medical education. Discussion Training in BBN will lead to improved patient and attendants' satisfaction, and empathetic support during difficult times.